Experimental study on the charging and discharging behaviour of capric–lauric acid/oleic acid mixture in a cold thermal energy storage system for cold storage applications. (2021) - Karthikeyan, K.; Mariappan, V.; Anish, R.; Sarafoji, P.; Jaya Bharata Reddy, M.
Abstract: In this study a capric–lauric acid/oleic acid mixture was synthesized to form a low temperature PCM for cold storage applications. An experimental investigation was carried out in a double helical coil cold thermal energy storage unit (CTESU) to study the charging and discharging behaviour of capric–lauric acid/oleic acid mixture. The inlet temperature and flow rate of the heat transfer fluid (HTF) were selected as experimental parameters to analyse the cold thermal energy storage performance of PCM. The analysis includes charging and discharging behaviour, energy dissipation rate, energy storage rate, energy charging efficiency, energy discharging efficiency and influence of HTF inlet temperature and flow rate under varied experimental parameters. With the increased contact area, the developed double helical coil considerably improves the heat transfer performance of the cold thermal energy storage unit. The discharging rate was 18% faster than the charging process due to predominance of natural convection. The PCM solidification during charging process is controlled by conduction. With increasing HTF flow rate during the discharging process, the melting rate was 16% higher than lower flow rates. In contrast, as flow rates increased, the charging rate did not change significantly. The role of natural convection and stratification which leads to unnecessary mixing of PCM consequently lowering the cooling energy stored. Also results suggest that capric–lauric acid/oleic acid can be utilized as a potential PCM for low temperature storage applications.